2013
DOI: 10.1242/jcs.131060
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Rac by Asef2 promotes myosin II-dependent contractility to inhibit cell migration on type I collagen

Abstract: SummaryNon-muscle myosin II (MyoII) contractility is central to the regulation of numerous cellular processes, including migration. Rho is a well-characterized modulator of actomyosin contractility, but the function of other GTPases, such as Rac, in regulating contractility is currently not well understood. Here, we show that activation of Rac by the guanine nucleotide exchange factor Asef2 (also known as SPATA13) impairs migration on type I collagen through a MyoII-dependent mechanism that enhances contractil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 63 publications
(89 reference statements)
2
38
0
Order By: Relevance
“…We had previously shown that these Asef2 shRNAs decrease endogenous expression of Asef2 by approximately 65% in HT1080 cells. 12,13 Transfection of Asef2 shRNA 1 or Asef2 shRNA 2 into HT1080 cells caused a significant increase in the migration speeds of these cells in 3D collagen I matrices compared to that observed with a non-targeting shRNA (NT shRNA) (Fig. 2C), indicating that knockdown of endogenous Asef2 promotes migration in 3D collagen I matrices.…”
Section: Resultsmentioning
confidence: 82%
See 4 more Smart Citations
“…We had previously shown that these Asef2 shRNAs decrease endogenous expression of Asef2 by approximately 65% in HT1080 cells. 12,13 Transfection of Asef2 shRNA 1 or Asef2 shRNA 2 into HT1080 cells caused a significant increase in the migration speeds of these cells in 3D collagen I matrices compared to that observed with a non-targeting shRNA (NT shRNA) (Fig. 2C), indicating that knockdown of endogenous Asef2 promotes migration in 3D collagen I matrices.…”
Section: Resultsmentioning
confidence: 82%
“…These results collectively show that Asef2 inhibits migration in 3D collagen I matrices, which is consistent with our previous observation on 2D collagen I substrates. 13 We have previously shown that Asef2 hinders migration on 2D collagen I through a mechanism that is dependent on Asef2 augments Rac activity in 3D collagen I matrices. Left, GFP and GFP-Asef2 cells were transfected with FLAG-Rac1 cDNA.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations